Internalizing Religious Behavior Through Philosophical Engagement: A Case Study at Miftahul Ulum Islamic Institute, Indonesia - Hafizh Idri Purbajati; Muhaiminah Darajat (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study explores the internalization of religious behavior among students through philosophical engagement at Miftahul Ulum Islamic Institute. Employing a qualitative field research design, data were collected via participant observation and in-depth interviews with selected students. Analysis followed the Miles and Huberman framework, comprising data reduction, display, and verification. Findings reveal that daily practices such as communal prayers, Qur'an recitation, and philosophical discourse are critical in shaping religious consciousness. The results contribute to understanding religious behavior formation through social and philosophical enculturation in Islamic higher education settings. The methods used are group methods and individual methods. This change in religious behavior is categorized as a change through the enculturation process.